Epidemiology of Zoonotic Gastrointestinal Helminths in Stray and Pet Dogs of Dhangadhi, Nepal - Bhatta, Laxman; Pokhrel, Shekhar; Khatri-Chhetri, Rupak (Journal of Agriculture and Forestry University, 2026)
Dogs act as reservoirs of zoonotic gastrointestinal helminths, posing a significant public health risk. A cross-sectional study was conducted in Dhangadhi City, where fecal samples from 400 dogs (200 pet, 200 stray) were examined for gastrointestinal helminths. Of all samples, 173 (43.25%) fecal samples showed the presence of at least one parasite. Stray dogs showed a significantly higher prevalence (p0.05) in pet dogs under 1 year (25%) compared to those over 1 year (22.4%). Single helminth infection was statistically significantly (p0.05) in male dogs than in females. The prevalence of zoonotic helminths was statistically significantly greater (p